Normal direction of flux distribution in the mix 60° - 23° T-joint of three phase transformer core - Fijay, Fauzi; Dina Maizana, Maiz Ahmad (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/